The Utility of Duplex Ultrasonography Surveillance in Identifying Failing Aortobifemoral Grafts. (August 2021) - Maloni, Krystal; Calligaro, Keith D.; Madden, Nicholas; Troutman, Douglas; Vani, Kunal; Dougherty, Matthew J.
Objective: The Society for Vascular Surgery stated there are a lack of studies describing long-term surveillance for aortobifemoral (AoBF) bypasses. Our goal was to investigate the value of DU studies as a surveillance tool for AoBF bypasses. Methods: We retrospectively identified patients in our prospectively maintained database who underwent AoBF bypasses between 1995-2018. Surveillance was performed routinely with DU post-operatively, every 6 months for 1 year, and then annually. We considered "abnormal" DU findings to include peri-graft fluid, pseudoaneurysm or, peak systolic velocities (PSVs) > 350 cm/sec or PSV ratio > 3.5 anywhere from the proximal aortic to distal femoral anastomosis. If abnormalities were identified patients underwent intervention or shorter surveillance intervals. Results: Of 153 AoBF bypasses, 60 patients with 120 graft limbs fulfilled our post-operative surveillance protocol with a mean follow-up of 4.0 years (0.5-24 years). "Normal" DU surveillance studies were documented throughout follow-up in 112 (93%) limbs. Of these, 2 (1.7%) developed acute limb occlusion. Eight (6.7%) limbs had "abnormal" DU findings: 5 failing grafts with focal elevated PSVs, 2 with peri-graft fluid leading to a diagnosis of an infected graft, and 1 with a pseudoaneurysm (PSA). Contrast arteriography or CT-angiography confirmed > 75% diameter stenosis, fluid or PSA in all 8 limbs. Graft revision (5 endovascular, 2 surgical) was performed in 7 of the 8 limbs initially or after 2 successive "abnormal" DU studies within 6 weeks of each other; 1 patient refused intervention. Without surveillance, urgent or emergent treatment might have proved necessary in 7.5% (7 + 2 = 9/120) of cases instead of only 1.7% (2/120) of cases. Conclusion: Vascular surgeons should adopt DU as a useful surveillance tool to identify AoBF bypasses that are failing or have other problems not identified clinically. Persistence of "abnormal" DU findings should prompt operative or endovascular intervention.